COMPARATIVE ANALYSIS OF PHYSICAL ENVIRONMENT, FOOD QUALITY AND PRICE FAIRNESS BETWEEN MALE AND FEMALE CUSTOMERS OF JAPANESE FOOD RESTAURANTS IN MANADO TOWN SQUARE - Monareh, Pascal A.A; Worang, Frederik G.; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Development of restaurant industry is growing rapidly in Indonesia resulted in developing Japanese Food Restaurants. Ichiban Sushi, Marugame Udon, Torico and Pepper Lunch are Japanese Food Restaurants located in Manado Town Square compete to give satisfaction to the customers. Physical Environment, Food Quality and Price Fairness have impact to the Customer Satisfaction which affects the repurchase intention of the customers and gaining profit. The purpose of this research is to analyze the differences between male and female customers of Japanese food restaurants in Manado Town Square determined from factors such as Physical Environment, Food Quality and Price Fairness. The Respondents are 100 customers of Japanese Food Restaurants in Manado Town Square divided by 50 male and 50 female. By using Independent Sample t-Test it shows that there is significant difference between male and female customers in Food Quality and Price Fairness meanwhile there is no significant difference between male and female customers in Physical Environment. For restaurateurs and managers, they should create new menu which suit male customers and pay attention to the food quantity. Thus, the price will become reasonable for the customers. They should upgrade their physical appearance so the customers will not get bored with the environment.Keywords: Physical Environment, Food Quality, Price Fairness, Independent Sample t-Test, Restaurant